New tetraphyllidean and trypanorhynch cestodes from deep sea skates in the western north atlantic - Campbell, R. A. (Proceedings of the Helminthological Society of Washington, 1977)
Two new tetraphyllidean cestodes, Echeneibothrium pollonae sp. nov. and Onchobothrium magnum sp. nov., are described from Bathyraja richardsoni (Garrick 1961) taken in the vicinity of Hudson Submarine Canyon. A new trypanorhynch, Grillotia (Paragrillotia) rowei sp. nov., is described from plerocerci recovered from Coryphaenoides (Nematonurus) armatus (Hector 1875) and an immature adult from the spiral valve of B. richardsoni. Echeneibothrium dubium abyssorum ssp. nov. is described from Raja radiata Donovan 1807, and represents an example of parasitism by a congener in a different part of the host's geographic range. Additional specimens of E. bathyphilum Campbell 1975 from R. bathyphila Holt and Byrne 1908 are reported.